Lupus nephritis: A focus on the United Arab Emirates and the potential role of genetics. (October 2022) - Tabouni, Mohammed; Ali, Amanat; Aljaberi, Najla; Alblooshi, Hiba
Lupus nephritis (LN) is a severe manifestation of systemic lupus erythematosus (SLE), characterized by chronic and progressive inflammation of the kidneys. As with many other autoimmune diseases, LN is a multifactorial disease caused by genetic and environmental factors. Globally, LN can affect around 60% of SLE patients, and it was observed to be less frequent and severe in Caucasian patients compared to other ethnic groups, including Arabs. Data on LN in the United Arab Emirates (UAE) are scattered and scarce in literature. Nevertheless, LN is common, occurring in around 43%–55% of SLE patients in the UAE. Anecdotally, the demographics and clinical features of SLE in the UAE have been distinct. However, the paucity of supporting literature makes it difficult to draw meaningful conclusions. Over the past two decades, there have been improvements in understanding the pathogenesis of LN; however, many cellular and molecular mechanisms which are implicated in the disease development and progression remain ambiguous. Investigating the clinical, pathological, and genetic characteristics of LN in different cohorts of patients is of importance for a better understanding of its pathogenesis, and thus improving its outcome. As a result, we acknowledge the need for large-scale epidemiological, clinical, and genetic investigation of LN cohorts in the UAE and surrounding regions.